Enhancing Cognitive Learning Outcomes in MA Al Manar Class XII MIA Students using a Problem-Based Learning Method on Biotechnology Materials - Sahidin, Ujang; Ratnasari, Jujun (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: Classroom action research aims to determine the application of problem-based learning methods to biotechnology material in improving cognitive learning outcomes for students in class XII MIA MA Al Manar Purwakarta. Methods: This study was carried out in class XII MIA MA Al Manar Purwakarta, which is located on Jalan Purnawarman Barat No. 71 in Purwakarta. The author had 21 students participate in this study as respondents. The method implemented in classroom action research is problem-based learning. This study's instruments included observation sheets, questionnaires, field notes, and tests. Results: Based on the research conducted, there was a significant increase in the value of biology from 23.81% to 80.95% between the odd semester and even semester of the 2021-2022 school year. Conclusion: Thus, the results of this study can improve students' cognitive learning outcomes. Keywords : Classroom action research; problem based learning method